Oxytocin receptors in the nucleus accumbens shell are necessary for the onset of maternal behavior - Witchey, Shannah; Haupt, Alexandra; Caldwell, Heather K. (Frontiers in Neuroscience, 2024)
IIn rodents, oxytocin (Oxt) contributes to the onset of maternal care by shifting the perception of pups from aversive to attractive. Both Oxt receptor knockout (Oxtr −/−) and forebrain-specific Oxtr knockout (FB/FB) dams abandon their first litters, likely due to a failure of the brain to ‘switch’ to a more maternal state. Whether this behavioral shift is neurochemically similar in virgin females, who can display maternal behaviors when repeatedly exposed to pups, or what neuroanatomical substrate is critical for the onset of maternal care remains unknown. To understand similarities and differences in Oxtr signaling in virgin pup-sensitized Oxtr FB/FB as opposed to post-parturient Oxtr −/− and Oxtr FB/FB dams, maternal behavior (pup-sensitized females only) and immediate early gene activation were assessed. Pup-sensitized Oxtr FB/FB females retrieved pups faster on day one of testing and had reduced c-Fos expression in the dorsal lateral septum as compared to virgin pup-sensitized Oxtr +/+ females. This differs from what was observed in post-parturient Oxtr −/− and Oxtr FB/FB dams, where increased c-Fos expression was observed in the nucleus accumbens (NAcc) shell. Based on these data, we then disrupted Oxtr signaling in the NAcc shell or the posterior paraventricular thalamus (pPVT) (control region) of female Oxtr floxed mice using a Cre recombinase expressing adeno-associated virus. Knockout of the Oxtr only in the NAcc shell prevented the onset of maternal care post-parturient females. Our data suggest that a pup-sensitized brain may differ from a post-parturient brain and that Oxtr signaling in the NAcc shell is critical to the onset of maternal behavior.